Differences in Liver Injury and Trophoblastic Mitochondrial Damage in Different Preeclampsia-like Mouse Models - Han, Yi-Wei; Yang, Zi; Ding, Xiao-Yan; Yu, Huan (Chinese medical journal, 2015)
Background：Preeclampsia is a multifactorial disease during pregnancy.Dysregulated lipid metabolism may be related to some preeclampsia.We investigated the relationship between triglycerides （TGs） and liver injury in different preeclampsia-like mouse models and their potential common pathways.Methods：Preeclampsia-like models （Nw-nitro-L-arginine-methyl ester [L-NAME],lipopolysaccharide [LPS],apolipoprotein C-Ⅲ [Apo] transgnic mice ＋ L-NAME,β2 glycoprotein Ⅰ [βGPI]） were used in four experimental groups：L-NAME （LN）,LPS,Apo-LN and βGPI,respectively,and controls received saline （LN-C,LPS-C,Apo-C,βGPI-C）.The first three models were established in preimplantation （PI）,early-,mid-and late-gestation （EG,MG and LG）.βGPI and controls were injected before implantation.Mean arterial pressure （MAP）,24-hour urine protein,placental and fetal weight,serum TGs,total cholesterol （TC） and pathologic liver and trophocyte changes were assessed.Results：MAP and proteinuria were significantly increased in the experimental groups.Placenta and fetal weight in PI,EP and MP subgroups were significantly lower than LP.Serum TGs significantly increased in most groups but controls.TC was not different between experimental and control groups.Spotty hepatic cell necrosis was observed in PI,EG,MG in LN,Apo-LN and βGPI,but no morphologic changes were observed in the LPS group.Similar trophoblastic mitochondrial damage was observed in every experimental group.Conclusions：Earlier preeclampsia onset causes a higher MAP and urine protein level,and more severe placental and fetal damage.Preeclampsia-like models generated by varied means lead to different changes in lipid metabolism and associated with liver injury.Trophoblastic mitochondrial damage may be the common terminal pathway in different preeclampsia-like models.